Предмет: Алгебра,
автор: maksimkolesnikov08
(4 − 1)(4 + 1) =
(8 + 2 )(2 − 8) =
( − 2 )(2 + ) =
(3 − 2 )(2 + 3 ) =
(−7 + 3 )(7 + 3 ) =
( 2 + 6)(6 − 2) =
(9 + 2)(− 2 + 9 ) =
(4 2 + 3)( 3 − 4 2) =
(5 2 + 2 )( 2 − 5 2 ) =
(8 + 7 3)(7 3 − 8 ) =
( 4 − 2)( 4 + 2) =
(2 + 3 )(2 − 3 ) =
ПОМОГИТЕ
Ответы
Автор ответа:
1
Ответ:
(4−1)(4+1) =3*5=15
(8+2)(2−8) =10*(-6)=-60
(−2)(2 +) =-4
(3−2)(2+3) =1*5=5
(−7+3)(7+3) =-4*10=-40
(2+6)(6−2) = 8*4=32
(9+2)(−2+9 ) =11*7=77
(42+3)(3−42) =-1755
(52+2 )(2−52 ) =54*(-50)=-2700
(8 + 7 3)(7 3−8 ) =81*65=5265
(4−2)(4+2) =2*6=12
(2+3 )(2−3 ) =5*1=5
Объяснение:
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Алина20051н
Предмет: Английский язык,
автор: ollik03
Предмет: Русский язык,
автор: киборг4
Предмет: География,
автор: bekeshovildar
Предмет: Українська мова,
автор: millkivay095